Parques públicos em área turística, forma jurídica e função social: estudo de caso Parque do Palácio (Canela/RS) - Frota, Ícaro da Silveira (My University, 2022)
The theme of this research is to analyze the legal modalities applicable as solution to keep public parks in operation in tourist areas, reaching the fulfillment of the social function. This is a case study on what happens to the Parque do Palácio located in Canela/RS due to its closing to the public in 2015 under the justification of lack of financial resources for its maintenance. The content disposition was divided into three main blocks: the first is dedicated to analyzing the Parque do Palácio through the historical, social, political and legal prism, providing such analysis to the future understanding of the possibilities of use and forms maintenance of the Parque do Palácio suggested at the end. Such suggestions are supported by the second main point, which deals with the insertion of Parque do Palácio to serve the social function, followed by the third and final point that presents an evaluative debate between the legal modalities considered capable of solving the problem presented, exploring advantages and disadvantages of each one, in order to, at the end, present a conclusion linked to this structure. The legal context of framing public parks is analyzed, what is its classification as a type of property and, finally, what is the most adequate legal modality to achieve its expected social function. Three legal models that were considered capable of solving the issue are visited: a) collective use through zoning that so determines; b) conversion of the space into an area of special tourist interest; or c) a transformation that would take it to the status of a Park, as defined by Law n. 9.985/00, that regulates art. 225, § 1, items I, II, III and VII, of the Brazilian Federal Constitution of 1988, establishing the National System of Nature Conservation Units. The research uses the inductive/investigative method from an example (case), through the deductive method of learning: exploratory, descriptive and explanatory because it particularizes conclusions, with a qualitative approach and procedure or technique of documentary bibliographic research. As for the purpose, it is applied research, as it is aimed at answering the problems raised by capturing the essential aspects that involve the proposed context. The investigation is linked to the research line "Environmental Law, Public Policies and Socio-Economic Developmen" for studying different existing legal frameworks, applicable as possible solutions to the problem under development. The study is justified in view of its legal relevance, being a controversial issue that involves a question of competence, ownership of the public good, political and social issues and also the academic insertion in the municipal community provided by a case study.
Esta pesquisa tem por tema analisar as modalidades jurídicas aplicáveis como solução para manter em funcionamento parques públicos em áreas turísticas, atingindo-se o cumprimento da função social. Trata-se de estudo de caso quanto ao que ocorre com o Parque do Palácio de Canela/RS em razão de seu fechamento ao público no ano de 2015 sob a justificativa de falta de recursos financeiros à sua manutenção. A divisão da disposição do conteúdo se deu em três blocos principais: o primeiro se dedica a analisar o Parque do Palácio de Canela/RS pelo prisma histórico, social, político e jurídico, prestando-se tal análise à compreensão futura das possibilidades de utilização e formas de manutenção do Parque sugeridas ao final. Tais recomendações são sustentadas pelo segundo ponto principal, que trata da inserção do Parque do Palácio de Canela/RS no atendimento da função social, seguido do terceiro e derradeiro ponto, que apresenta debate valorativo entre as modalidades jurídicas consideradas aptas a solucionar o problema apresentado, ventilando-se vantagens e desvantagens de cada uma para, ao final, ser apresentada conclusão atrelada a esta estrutura. Percorre-se o contexto legal de enquadramento de parques públicos, qual sua classificação enquanto tipo de propriedade e, por fim, qual a modalidade jurídica mais adequada para atingir a função social dele esperada. São visitados três modelos jurídicos que se entende como capazes de solucionar a questão: a) uso coletivo através de zoneamento que assim determine; b) conversão do espaço em área de especial interesse turístico; ou, ainda, c) uma transformação que o levasse à condição de Parque, nos moldes definidos pela Lei no 9.985/00, que regulamenta o art. 225, § 1o, incisos I, II, III e VII, da Constituição Federal Brasileira de 1988, instituindo o Sistema Nacional de Unidades de Conservação da Natureza. A pesquisa utiliza-se do método indutivo/investigativo a partir de um exemplo(caso), mediante o método dedutivo de aprendizagem: exploratório, descritivo e explanatório, pois particulariza conclusões, com abordagem qualitativa e procedimento de pesquisa bibliográfica documental. Quanto à finalidade, trata-se de pesquisa aplicada, uma vez que dirigida a responder os problemas levantados captando os aspectos essenciais que envolvam o contexto proposto. A investigação se vincula à linha de pesquisa "Direito Ambiental, Políticas Públicas e Desenvolvimento Socioeconômico" por estudar diferentes moldes jurídicos existentes, aplicáveis como possíveis soluções ao problema em fomento. O estudo se justifica ante a relevância jurídica, sendo tema polêmico que envolve questão de competência, de titularidade do bem público, questões políticas/sociais e, também, pela inserção acadêmica junto à comunidade municipal propiciada por um estudo de caso. [resumo fornecido pelo autor]
Keywords: Direito de propriedade; Parques - Aspectos jurídicos; Parques - Canela (RS).; Right of property; Parks - Legal aspects; Parks - Canela (Brazil)